Pemberdayaan Kelompok Pengelola Wisata Dalam Upaya Peningkatan Pemanfaatan Wisata Mangrove di Desa Kedungasri Kecamatan Tegaldlimo Kabupaten Banyuwangi - Munawir Munawir; Mahbub Mahbub; Masnida Masnida (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
Based on field studies, there are several problems faced by the community in Kedungasri Village, Dusun Persen, especially the Kaliwatu hamlet community, Tegaldlimo District, Banyuwangi Regency, including: 1) Lack of community response to the development of mangrove tourism. 2) Lack of public insight into the benefits of mangrove forests. 3) The mindset of society that is less advanced, innovative, and creative. 4) Lack of group group management of mangrove tourism. After the socialization of the program "Renovation of mangrove tourism facilities" which was followed by the community around the mangrove tourism, it had a positive impact on resolving the problem of renovating the tourist facilities, this empowerment received a positive response from the Kaliwatu hamlet community because it beautified the mangrove tourism in the Kaliwatu hamlet, Dusun Persen. Kedungasri Village, Tegaldlimo District, Banyuwangi Regency.